Urbanization, Economic Activity, and Electricity Consumption in Jordan: Evidence from the ARDL Approach - Alawneh, Ateyah Mohammad Ateyah (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of urbanization on per capita electricity consumption in Jordan, while controlling for key economic and structural determinants, namely economic growth, industrial sector contribution, and population growth. Using annual time-series data for the period 2000–2022, the study employs the Autoregressive Distributed Lag (ARDL) methodology to analyze both short-run dynamics and long-run equilibrium relationships among the variables. The results of the ARDL bounds testing procedure confirm the existence of a long-run cointegrating relationship between electricity consumption and its underlying determinants. Long-run estimates reveal that urbanization, economic growth, industrial sector contribution, and population growth all exert positive and statistically significant effects on per capita electricity consumption. These findings indicate that urban expansion and structural economic transformation are key drivers of the increasing electricity demand in Jordan. In the short run, the error correction model (ECM) reveals significant dynamic adjustments. Urbanization and industrial activity exert immediate and positive effects on electricity consumption, whereas economic growth displays mixed short-term impacts. The error correction term is negative and statistically significant, confirming the stability of the long-run equilibrium and indicating a relatively rapid adjustment process following short-term disturbances. The study concludes that accelerated urbanization and economic expansion place increasing pressure on Jordan’s electricity sector. Accordingly, policymakers are encouraged to integrate energy efficiency initiatives, sustainable urban planning practices, and industrial energy management strategies to ensure long-term energy security and environmental sustainability.